Air Attack Against Wildfires Understanding U.S. Forest Service Requirements for Large Aircraft - Keating, Edward G. (RAND Corporation, 2012)
A RAND study sought to help the U.S. Forest Service determine the composition of a fleet of airtankers, scoopers, and helicopters that would minimize the total social costs of wildfires, including the cost of large fires and aircraft costs. The research team developed two models to estimate the social cost-minimizing portfolios of firefighting aircraft. Both models favored a fleet dominated by scoopers for the prevention of large fires.